PENGARUH PEMASARAN RELASIONAL TERHADAP LOYALITAS PELANGGAN PADA PT NAGAMAS MITRA SEJATI TEGAL - Nurhadi Kamaluddin; Ari Susantiaji; Siti Amalia (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
Relational marketing is one of the marketing strategies used by companies to maintain good long-term relationships with customers. This study aims to determine the partial and simultaneous effect of trust, commitment, and communication variables on customer loyalty at PT Nagamas Mitra Sejati Tegal. Methods of data collection using observation, questionnaires, and literature study. In this study, the population is consumers who have purchased a Honda motorcycle at PT Nagamas Mitra Sejati Tegal in January 2021, as many as 132 consumers. The sampling technique used was accidental random sampling with a sample size of 100 respondents. The analysis technique of the data used quantitative qualitative and then analyzed with multiple regression analysis techniques. Hypothesis testing using a t-test shows that partially the three independent variables studied affect the dependent variable. Then through the f test, the three independent variables simultaneously affect the dependent variable, namely customer loyalty. The conclusion is that partially and simultaneously, the variables of relational marketing, which consist of trust, commitment, and communication, influence customer loyalty at PT Nagamas Mitra Sejati Tegal. The dominant factor influencing customer loyalty at PT Nagamas Mitra Sejati Tegal is communication.